Sinergi Satpol PP dan Masyarakat dalam Penegakan Peraturan Daerah: Studi Empiris tentang Partisipasi Publik di Kecamatan Sagulung - Muhammad Arif; Dwi Afni Maileni; Rabu Rabu; Rizki Tri Anugrah Bhakti (Siber Nusantara Publisher, 2026)
This study aims to analyze the synergy between the Civil Service Police Unit (Satpol PP) and the community in enforcing regional regulations in Sagulung District, Batam City, with particular emphasis on the forms of public participation, coordination mechanisms, and their impact on the effectiveness of public order enforcement. The study employed a qualitative descriptive approach. Data were collected through field observation and documentation of collaborative practices between Satpol PP and local residents in supporting the enforcement of regional regulations. The findings show that such synergy is built through two-way communication patterns, formal complaint channels, local coordination forums, and the involvement of community leaders, neighborhood associations, community protection units, and residents in monitoring, reporting, prevention, and assistance during enforcement activities. Community participation was found to accelerate the detection of violations, improve Satpol PP’s responsiveness, strengthen public compliance, and reduce the potential for conflict during enforcement processes. However, the effectiveness of this collaboration remains constrained by several inhibiting factors, including uneven legal awareness among citizens, limited institutional resources, and the lingering repressive image of enforcement officers. This study concludes that regional regulation enforcement becomes more effective when implemented through a participatory partnership model that positions the community not merely as an object of regulation, but as an active subject sharing responsibility for maintaining public order.